2023
DOI: 10.1097/dcr.0000000000002466
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Immune Checkpoint Inhibition Improves Organ Preservation in T4bM0 Colorectal Cancer With Mismatch Repair Deficiency: A Retrospective Observational Study

Abstract: BACKGROUND:Colorectal cancer with mismatch repair deficiency is usually less aggressive and associated with a lower risk of distant metastasis. Immune checkpoint inhibition, rather than traditional chemoradiotherapy, has shown great advantages in treating such patients. OBJECTIVE:This study aimed to verify the hypothesis that locally very advanced (T4b) colorectal cancer without distant metastases might present with higher probability of mismatch repair deficiency and be more sensitive to neoadjuvant immune ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…A retrospective study of 245 patients with CRC showed that the incidence of MSI-H was higher in patients with right colon cancer and TNM stage I-II disease (30). Another retrospective analysis of 268 patients with CRC showed a high incidence of dMMR in patients with locally advanced (T4b) tumors without distant metastasis (31). Additionally, a recent analysis of 1,014 patients with CRC (100 [9.8%] with dMMR and 914 [90.2%] with pMMR tumors) indicated that advanced-stage tumors were significantly more common among patients with pMMR CRC than among those with dMMR CRC (stage IV: 21% vs. 3%; P < 0.001) (27).…”
Section: Demographic Characteristics and Msi/mmr Status In Crcsmentioning
confidence: 99%
“…A retrospective study of 245 patients with CRC showed that the incidence of MSI-H was higher in patients with right colon cancer and TNM stage I-II disease (30). Another retrospective analysis of 268 patients with CRC showed a high incidence of dMMR in patients with locally advanced (T4b) tumors without distant metastasis (31). Additionally, a recent analysis of 1,014 patients with CRC (100 [9.8%] with dMMR and 914 [90.2%] with pMMR tumors) indicated that advanced-stage tumors were significantly more common among patients with pMMR CRC than among those with dMMR CRC (stage IV: 21% vs. 3%; P < 0.001) (27).…”
Section: Demographic Characteristics and Msi/mmr Status In Crcsmentioning
confidence: 99%
“…These findings could indicate tumor downstaging with neoadjuvant chemotherapy. Some research has shown promising results with regard to colon cancer downstaging with NAT 19,20 . However, these results should be examined carefully as the higher proportion of T4 tumors in the SRF group may indicate patients presenting with obstructive or near‐obstructive symptoms and cannot tolerate NAT.…”
Section: Discussionmentioning
confidence: 99%
“…From these, 8 studies met the eligibility criteria. [11][12][13][14][15][16][17][18] No new studies were included in the PubMed search between April and September 2023. A flow diagram is in Supplemental Figure 1 at http://links.…”
Section: Systematic Reviewmentioning
confidence: 99%